Hermogenes and the doctrine of the origin of the world from eternal matter in Tertullian’s Adversus Hermogenem - Glowacki, Marc-Thilo (Filozofia Chrześcijańska, 2024)
The aim of this article is to reconstruct and describe the cosmology of Hermogenes of Carthage, an early Christian theologian of Greek and Syrian origin. A secondary objective is to verify the available accounts on his teachings found in the works of Christian writers, especially Tertullian. The analysis of this issue starts by presenting the accounts and his biography. Subsequently, I present and analyse his concept of matter, followed by its relation to God and the act of creation. Finally, I focus on the interpretation of the biblical accounts on the world’s origin. I conduct the study using methods of literary studies, especially the hermeneutic and phenomenological methods. The main conclusion of this article is that Hermogenes, as a theologian, was a Christian Platonist and not a member or leader of a gnostic movement. Secondly, his ideas on matter and evil refl ect the contemporary views of many Mediterranean authors and philosophers. The research is based on Tertullian’s Adversus Hermogenem supplemented with Hippolytus’s Refutatio, as well as available texts of Platonic philosophers. This text sheds additional light on the issue of the adaptation of Platonic philosophy in early Christian theology.